2017
DOI: 10.1093/gbe/evx162
|View full text |Cite
|
Sign up to set email alerts
|

The Environmental Acinetobacter baumannii Isolate DSM30011 Reveals Clues into the Preantibiotic Era Genome Diversity, Virulence Potential, and Niche Range of a Predominant Nosocomial Pathogen

Abstract: Acinetobacter baumannii represents nowadays an important nosocomial opportunistic pathogen whose reservoirs outside the clinical setting are obscure. Here, we traced the origins of the collection strain A. baumannii DSM30011 to an isolate first reported in 1944, obtained from the enriched microbiota responsible of the aerobic decomposition of the resinous desert shrub guayule. Whole-genome sequencing and phylogenetic analysis based on core genes confirmed DSM30011 affiliation to A. baumannii. Comparative studi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

8
62
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1
1

Relationship

2
7

Authors

Journals

citations
Cited by 40 publications
(70 citation statements)
references
References 89 publications
8
62
0
Order By: Relevance
“…The overall observations for a number of representative strains are summarized in Figure 3 (see Table S1 and Table S2 for further details). In agreement with other studies using different sets of core genes and phylogenetic strategies (1, 4, 8, 41), the A. baumannii strain cluster is clearly demarcated in the ML tree of Fig. 3 from those composed of its phylogenetically closely-related ACB species including A. nosocomialis, A. seifertii, A calcoaceticus, A. oleivorans , and A. pittii , which are in turn well-differentiated between them.…”
Section: Resultssupporting
confidence: 90%
See 1 more Smart Citation
“…The overall observations for a number of representative strains are summarized in Figure 3 (see Table S1 and Table S2 for further details). In agreement with other studies using different sets of core genes and phylogenetic strategies (1, 4, 8, 41), the A. baumannii strain cluster is clearly demarcated in the ML tree of Fig. 3 from those composed of its phylogenetically closely-related ACB species including A. nosocomialis, A. seifertii, A calcoaceticus, A. oleivorans , and A. pittii , which are in turn well-differentiated between them.…”
Section: Resultssupporting
confidence: 90%
“…A V4_1 sub-variant displaying the shorter QQAQ C-terminal end was found in the A. baumannii DSM30011 strain (Table 1 and Table S2). DSM30011 was isolated before 1944 from a desert plant source and, in agreement with an environmental origin, is susceptible to most clinically-employed antimicrobials including folate synthesis inhibitors (41).…”
Section: Resultsmentioning
confidence: 97%
“…In agreement with other studies using different sets of core genes and phylogenetic strategies [1,2,9,54,60] the cluster formed by A. baumannii strains/isolates was clearly demarcated in the ML tree from those composed of its phylogenetically closely related ACB species including A. nosocomialis,…”
Section: Intra-and Inter-species Exchange Of Ompa Variantssupporting
confidence: 91%
“…Compared with the original study, we identified fewer bacterial genera (279 compared with 1,546) in this study, as we were only looking for whole genomes and had a higher threshold for detection 14 . We found that the most frequently observed genera in the 79 samples were genera that have previously been commonly observed in fecal (Streptococcus, Enterobacter, Bifidobacterium, Escherichia, Lactobacillus, Klebsiella) 17,18 and environmental samples (Acinetobacter, Pseudomonas, Acidovorax) [19][20][21] , and only Enterobacter and Lactobacillus among the top 10 were not present in the top 15 most abundant genera from the original study of this data 14 .…”
Section: Discussionmentioning
confidence: 65%